Ecological Characteristics of Water Bodies of Mining Regions (On the Example of the Irsha River of Zhytomyr Region) - Єльнікова, Т. О. (Київський національний університет імені Тараса Шевченка, 2021)
The urgency of the topic is determined by the importance of using the water of the Irsha River for various purposes: a source of drinking water, a source of energy, use it as a recreational facility, for irrigation, fishing, etc. The Irsha River is under the influence of the Irsha Mining and Processing Plant. When water infiltrates through the body of tailings dams, settling ponds, oxidized water enters surface waters. The aim of the research is the ecological assessment of the surface water quality of the Irsha River and the analysis of the impact of the mining industry on it. The task of the study is to analyze the impact on the state of surface waters of the river Irsha mining industry. The subject of the study is a set of hydrochemical and hydrological indicators of the ecological status of the river Irsha, left tributary of the Teteriv River (basin of Dnipro) in the Zhytomyr region for the period 2018-2019. The graphic method of complex assessment of water quality and the method of ecological assessment of surface water quality of the river Irsha according to the corresponding categories are applied in the work. The purpose of the study is the ecological assessment of the surface water quality of the Irsha River and the analysis of the impact of the mining industry on it. Analysis of the results of laboratory studies of the quality of wastewater discharged into the Irsha River indicates exceeding the established standards. This is due to the presence of pollutants in the soil that enter into the water. According to the results of a comprehensive assessment of surface water quality based on the graphical method, it was found that in 2018-2019 in general river waters in both observation sites within the Irsha River do not meet quality requirements, there were high values of MPC for dissolved oxygen, total iron and permanganate oxidation in both alignments. It is investigated that the surface waters of the river Irsha in both springs belong to the III class of water quality, which indicates a significant anthropogenic impact, the level of which is close to the limit of ecosystem stability. This is due to the high anthropogenic load in the Irsha river basin, primarily due to discharges of insufficiently treated wastewater. The results of research indicate a significant anthropogenic impact, the level of which is close to the limit of ecosystem sustainability. Given the current level of pollution of the Irsha River, the priority task in the field of environmental protection, rational use of natural resources is the implementation of measures provided by state and regional target programs to reduce anthropogenic pressure and improve surface water bodies.

Предметом дослідження є набір гідрохімічних та гідрологічних показників екологічного стану річки Ірша лівої притоки р. Тетерева (басейн Дніпра) у Житомирській області за період 2018-2019 рр. У роботі застосовано графічний метод комплексної оцінки якості води та методика екологічної оцінки якості поверхневих вод р. Ірша за відповідними категоріями. Метою дослідження є екологічна оцінка якості поверхневих вод р. Ірша та аналіз впливу на неї гірничодобувної промисловості. Висновки. За результатами комплексної оцінки якості поверхневих вод на основі графічного методу виявлено, що у 2018-2019 рр. в цілому річкові води в обох створах спостереження у межах р. Ірша не відповідають вимогам якості, спостерігалися високі значення показників кратності перевищення ГДК для показника ХСК, розчиненого кисню, заліза загального та перманганатної окиснюваності в обох створах. Досліджено, що поверхневі води р. Ірша в обох створах відносяться до ІІІ класу якості води, що свідчить про значний антропогенний вплив, рівень якого близький до межі стійкості екосистем.
Екологічна характеристика водних об’єктів гірничодобувних регіонів (на прикладі річки Ірша Житомирської області)
Keywords: екологічна оцінка; річка Ірша; гірничодобувна промисловість; ecological assessment; Irsha river; mining industry